Langdale Company 1994 Calendar - Langdale Forest Products Co. (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1994)
Langdale Company 1994 Calendar, printed for 100th Anniversary.
54 Scans. (JPG/TIFF). 1 PDF. MS/30 Langdale Collection.
Keywords: Langdale Forest Products Company; South Georgia Folklife Collection (Valdosta State University); Turpentine industry and trade; Calendars; Langdale, Harley, 1888-1972; Langdale, Harley, Jr., 1914-2013; Forest products industry